Statistics for business and economics - Mann, Prem S. (John Wiley and Sons, 1995)
Introduction. Organizing data. Numerical descriptive measures. Probability. Discrete random variables and their probability distributions. Sampling distributions. Estimation of the mean and proportion. Estimation and hypothesis testing.